Effect and Mechanism of 808 nm Light Pretreatment of Hypoxic Primary Neurons - Xin Chen; Qiang-Li Wang; Shuang Li; Xian-qiang Mi (International Journal of Photoenergy)
This study investigated the effect of low intensity 808 nm light pretreatment of hypoxic primary neurons. Cobalt chloride (CoCl2) has been used to induce hypoxic injury in primary mouse cortical neurons. Low intensity 808 nm light was from light-emitting diode (LED). Cells were randomly divided into 4 groups: normal control group, CoCl2-induced group, CoCl2-induced group with 808 nm light irradiation pretreatment, and normal group with 808 nm light irradiation pretreatment. Effect of low intensity 808 nm light on neuronal morphology has been observed by microscope. MTT colorimetric assay has been used to detect the effect of low intensity 808 nm light on neuronal activity. Adenosine triphosphate (ATP) concentration and cytochrome C oxidase (COX) activity has been detected to study the effect of low intensity 808 nm light on neuronal mitochondria function. The results indicated that low intensity 808 nm light pretreatment alone did not affect cell viability, COX activity, and ATP content of neurons and low intensity 808 nm light pretreatment promoted the cell viability, COX activity, and ATP content of neurons with CoCl2 exposure; however, low intensity 808 nm light pretreatment did not completely recover COX activity and cellular ATP content of primary neurons with CoCl2 exposure to the level of the normal neurons.